13 Innovation feed: the development of a web tool to support innovation at GOSH. (30th November 2020) - Bullough, Harry; Zhan, Guangpeng; Igandan, Emmanuel; Bassi, Daiana; Conner, Sue; Fu, Yun; Mohamedally, Dean; Molyneux, Gemma; Roberts, Graham; Sebire, Neil J; Oakes, Nina
Abstract : Innovation is incredibly important in the growth and development of any organisation. In healthcare, the sharing of best practice and innovative ideas has the capacity to bring about significant patient benefit. However, it can be difficult to share ideas and develop collaborations in busy, multi-disciplinary organisations. The aim of this project was to build a website to allow staff from across the organisation to share concepts and ideas for innovative projects. As part of a joint collaboration between GOSH, GOSH Children's Charity, and UCL computer science (CS), through the industry exchange network programme, a prototype website was developed using NodeJS with a MySQL database. The platform allows ideas to be proposed, commented on, and voted for by users. Calls for innovative ideas can be launched to address specific issues within the organisation. The prototype website was developed to support the GOSH Charity and Trust to encourage staff to share their innovation ideas as well as the achievements and barriers associated with existing, or previous, innovation and improvement projects. The website also aims to connect staff from across the organisation who are working on similar projects, to facilitate sharing of experiences, ideas and expand cross-departmental collaborations.